Interdependence of hypoxia and β-adrenergic receptor signaling in pulmonary arterial hypertension - Stephens, Olivia R. (Am J Physiol Lung Cell Mol Physiol, 2019)
The β-adrenergic receptor (βAR) exists in an equilibrium of inactive and active conformational states, which shifts in response to different ligands and results in downstream signaling. In addition to cAMP, βAR signals to hypoxia-inducible factor 1 (HIF-1). We hypothesized that a βAR-active conformation (R**) that leads to HIF-1 is separable from the cAMP-activating conformation (R*) and that pulmonary arterial hypertension (PAH) patients with HIF-biased conformations would not respond to a cAMP agonist. We compared two cAMP agonists, isoproterenol and salbutamol, in vitro. Isoproterenol increased cAMP and HIF-1 activity, while salbutamol increased cAMP and reduced HIF-1. Hypoxia blunted agonist-stimulated cAMP, consistent with receptor equilibrium shifting toward HIF-activating conformations. Similarly, isoproterenol increased HIF-1 and erythropoiesis in mice, while salbutamol decreased erythropoiesis. βAR overexpression in cells increased glycolysis, which was blunted by HIF-1 inhibitors, suggesting increased βAR leads to increased hypoxia-metabolic effects. Because PAH is also characterized by HIF-related glycolytic shift, we dichotomized PAH patients in the Pulmonary Arterial Hypertension Treatment with Carvedilol for Heart Failure trial (NCT01586156) based on right ventricular (RV) glucose uptake to evaluate βAR ligands. Patients with high glucose uptake had more severe disease than those with low uptake. cAMP increased in response to isoproterenol in mononuclear cells from low-uptake patients but not in high-uptake patients’ cells. When patients were treated with carvedilol for 1 wk, the low-uptake group decreased RV systolic pressures and pulmonary vascular resistance, but high-uptake patients had no physiologic responses. The findings expand the paradigm of βAR activation and uncover a novel PAH subtype that might benefit from β-blockers.